NATIONAL DATABASE OF METAL IN COMPARATIVE PERSPECTIVES OF THE UNITED KINGDOM & INDONESIA - rachma puspitasari; raldi koestoer (Marine Geological Institute of Indonesia, 2021)
The ocean is a source of mega-biodiversity that is supposed to perform optimally for current and future generations. The health of the ocean must be evaluated by measuring heavy metals in sediment because they can be accumulated and stored in long term. This metal can be released and absorbed by an organism, and affect the ecological risk and human health. The purpose of this article is to share viewpoints and those in a comparative study in terms of the metal database of both countries, the UK and Indonesia. The methodology used in this paper is critical review and analysis to compare a success story about compiling metal data into a national database in the United Kingdom (UK). Indonesia already has an open public access database issued by the Ministry of Environment and Forestry. The further step is to strengthen collaboration between research institutes, universities, and government to assign a Standard Operational Procedure (SOP) to collect, analyze and report the data to a national depository. This database will be worthwhile to describe the pollution status in Indonesia and basic data for best practice decisions.